Casting inner runner precoated sand mud core coating and preparation method thereof
By using phenolic resin, composite adhesive and other components in the casting inner runner coated sand and mud core coating, the problem of insufficient adhesion force of the paint under high temperature conditions is solved, and higher adhesion and thermal stability are achieved, which significantly improves the quality and safety of the castings.
Patent Information
- Application Number
- CN202411868104.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing coated sand and mud core coatings lack adhesion under high temperature conditions, resulting in roughness and reduction in the surface of the runner in the casting, which in turn affects the mechanical properties and safety of the castings.
The casting inner runner coating sand and mud core coating is used to form a continuous film structure with phenolic resin, composite adhesive, dispersant, defoaming agent, zircon powder and refractory filler. The composite adhesive improves the bonding strength, dispersant and defoaming agent ensure uniformity and reduction of defects, and zircon powder and refractory filler improve thermal stability and refractory performance.
It significantly improves the adhesion and thermal stability of the coating, reduces the defect rate caused by coating problems, and improves the overall quality and safety of the castings.
Smart Images

Figure BDA0005195017300000081 
Figure BDA0005195017300000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coated sand casting, and in particular to a coated sand mud core coating for an inner flow channel of a casting and a preparation method thereof. Background Art
[0002] In the precision casting process, the surface quality of the internal flow channel of the casting directly affects the overall performance and service life of the casting. Traditional casting internal flow channel molding usually uses graphite-based coatings, but due to its poor adhesion and easy peeling, it is easy to increase the porosity of the casting under high-temperature pouring conditions, seriously affecting the quality of the casting. In recent years, in order to improve this situation, researchers have begun to explore new coating systems, among which coated sand mud core coatings have attracted widespread attention due to their good high-temperature stability, demoulding and fire resistance.
[0003] However, although the existing coated sand mud core coating has improved the surface quality and molding accuracy of the inner flow channel of the casting to a certain extent, there is still a problem of insufficient adhesion. After being flushed by the molten metal during casting, the sand particles on the surface of the mud core loosen and fall off, increasing the surface roughness of the inner flow channel and reducing the smoothness, thereby reducing the mechanical properties of the casting and causing safety accidents. Therefore, it needs to be improved. Summary of the invention
[0004] In order to improve the adhesion of the coated sand-mud core coating, the present application provides a coated sand-mud core coating for an inner flow channel of a casting and a preparation method thereof.
[0005] The present application provides a casting inner flow channel coated sand mud core coating and a preparation method thereof, which adopts the following technical solutions: In the first aspect, the present application provides a casting inner flow channel coated sand mud core coating, which adopts the following technical solutions: A sand-mud core coating for coating inner flow channels of castings, comprising the following components in parts by mass: Phenolic resin 5-10 parts Composite adhesive 12-15 parts Dispersant 3-5 parts 1-2 parts of defoamer Zircon powder 20-30 parts Refractory filler 5-10 parts 20-30 parts of solvent; The composite binder comprises aluminum dihydrogen phosphate and water glass.
[0006] Phenolic resin can form a continuous and stable film structure, which can enhance the adhesion of the coating to the surface of the sand core. The aluminum dihydrogen phosphate and water glass in the composite binder cooperate with each other. The aluminum dihydrogen phosphate has good adhesion and high-temperature stability. The water glass fills the pores to form a tight bond. The two work together to improve the bonding strength between the coating and the sand core and enhance the stability of the coating in a high-temperature environment. The dispersant can evenly disperse the components to avoid agglomeration, ensure the consistency of the coating performance, and make the adhesion more uniform and stable. The defoamer can eliminate the bubbles generated during the preparation and use process, prevent the bubbles from forming defects in the coating, and improve the quality of the coating. Zircon powder has a high melting point and chemical stability, which can improve the high-temperature resistance and chemical corrosion resistance of the coating and further enhance the thermal stability. The refractory filler can improve the refractory performance of the coating, withstand the erosion of high-temperature molten metal, and reduce the damage of high temperature to the coating and sand core, thereby effectively improving the adhesion and thermal stability of the coating and reducing the defect rate of castings caused by coating problems.
[0007] Preferably, the phenolic resin is modified to obtain a modified phenolic resin, and the raw materials for preparing the modified phenolic resin include a phenolic resin body and an organosilicon resin.
[0008] Phenolic resin provides good adhesion and basic mechanical properties for the coating. The silicon-oxygen bonds in silicone resin can give the coating excellent heat resistance, oxidation resistance and chemical stability, which can effectively prevent the decomposition of the coating at high temperatures. At the same time, silicone resin can also improve the flexibility of phenolic resin, reduce the cracking of the coating caused by thermal stress or mechanical stress, enhance the adhesion of the coating to the sand core surface and its own interior, and further improve the stability of the coating in high temperature and complex environments, thereby improving the quality of the entire casting inner channel coating sand mud core coating and reducing the defect rate of the casting.
[0009] Preferably, the raw materials for preparing the silicone resin include dimethyldimethoxysilane, methylvinyldichlorosilane and phenyltrichlorosilane.
[0010] Dimethyldimethoxysilane can increase the flexibility of silicone resin and its solubility in the system. The methyl group can enhance the physical adsorption between the silicone resin and the bonded substrate, making it have better affinity with the substrate surface; methylvinyldichlorosilane introduces vinyl groups into the resin, which can participate in the cross-linking reaction and increase the cross-linking density of the resin, thereby enhancing the hardness and heat resistance of the resin; the phenyl group in phenyltrichlorosilane can improve the thermal stability, oxidation resistance and chemical inertness of the silicone resin, while giving the resin a better steric hindrance effect, reducing the freedom of movement of the molecular chain when heated, thereby inhibiting the thermal decomposition caused by excessive movement of the molecular chain, optimizing the performance of the resin in the coating, and thus enabling the silicone resin to better cooperate with the phenolic resin and improve the quality of the sand mud core coating for the inner flow channel of the casting.
[0011] Preferably, the mass ratio of dimethyldimethoxysilane, methylvinyldichlorosilane and phenyltrichlorosilane is 1:0.6:(0.5-0.7).
[0012] The organic silicone resin prepared according to the above mass ratio has good performance and can effectively improve the adhesion and thermal stability of the coating, thereby reducing the defect rate of the casting.
[0013] Preferably, the refractory filler comprises nano-alumina and silicon carbide microspheres.
[0014] Nano-alumina has high hardness, high melting point, good chemical stability and thermal stability, which can effectively enhance the coating's tolerance to high-temperature environments and resist the erosion of high-temperature molten metal; silicon carbide microspheres have excellent high-temperature resistance and chemical stability, and their special spherical structure helps to improve the dispersion of fillers in the coating. The two can work together to further improve the filling effect of refractory fillers in the coating, reduce the shrinkage and deformation of the coating at high temperatures, enhance the overall refractory performance of the coating, and ensure the stability and quality of the flow channel in the casting during the casting process, thereby reducing the defect rate of the casting.
[0015] Preferably, the mass ratio of the nano-alumina to the silicon carbide microspheres is 1:(0.3-0.5).
[0016] The refractory filler prepared according to the above ratio has a good synergistic effect and can effectively improve the thermal stability of the coating.
[0017] Preferably, the refractory filler is modified to obtain a modified refractory filler, and the modified refractory filler is prepared by the following steps: The nano-alumina and silicon carbide microspheres are mixed, ultrasonically washed with an ethanol aqueous solution, filtered and dried to obtain a washed refractory filler; the washed refractory filler is added to a silane coupling agent ethanol solution, stirred for reaction, ball milled, filtered to obtain a solid product, and dried to obtain a modified refractory filler.
[0018] The modified refractory filler prepared according to the above steps has good dispersibility and can effectively improve the thermal stability of the coating.
[0019] Preferably, the raw materials for preparing the sand mud core coating for coating the inner flow channel of the casting also include poly N-isopropyl acrylamide.
[0020] Poly (N-isopropylacrylamide) has unique temperature-sensitive properties. The conformation of its molecular chain changes at different temperatures. During the casting process, when the temperature rises, this change helps the coating to better adapt to the high temperature environment and enhance the thermal stability of the coating. At the same time, poly (N-isopropylacrylamide) can improve the rheological properties of the coating, making the coating easier to distribute evenly during the coating process, thereby improving the adhesion of the coating to the sand core surface, thereby reducing casting defects caused by uneven coating or poor performance at high temperatures and improving casting quality.
[0021] Preferably, the added amount of the poly (N-isopropylacrylamide) is 1-3% of the total mass.
[0022] Adding poly (N-isopropylacrylamide) in the above ratio can achieve good performance improvement, and the prepared coating has good adhesion and thermal stability.
[0023] In the second aspect, the present application provides a method for preparing a sand-mud core coating for coating an inner flow channel of a casting, using the following technical scheme: A method for preparing a sand-mud core coating for an inner flow channel of a casting, comprising the following steps: The phenolic resin is dispersed in a solvent and stirred until the phenolic resin is completely dissolved to obtain a phenolic resin solution; a composite binder is added to the phenolic resin solution, heated and stirred to obtain a binder solution; a dispersant and a defoamer are added to the binder solution and stirred to obtain a mixed solution; zircon powder and a refractory filler are added to the mixed solution, ball-milled and stirred to obtain a sand mud core coating for the inner flow channel of the casting.
[0024] The coating prepared according to the above steps has good performance, can reduce casting defects and improve the quality of castings.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Phenolic resin can form a continuous and stable film structure, which can enhance the adhesion of the coating to the surface of the sand core. The aluminum dihydrogen phosphate and water glass in the composite binder cooperate with each other. The aluminum dihydrogen phosphate has good adhesion and high temperature stability. The water glass fills the pores to form a tight bond. The two can work together to improve the bonding strength between the coating and the sand core and enhance the stability of the coating in a high temperature environment. The dispersant can evenly disperse the components to avoid agglomeration, ensure the consistency of the coating performance, and make the adhesion more uniform and stable. The defoamer can eliminate the bubbles generated during the preparation and use process, prevent the bubbles from forming defects in the coating, and improve the coating quality. Zircon powder has a high melting point and chemical stability, which can improve the high temperature resistance and chemical corrosion resistance of the coating and further enhance the thermal stability. The refractory filler can improve the refractory performance of the coating, withstand the erosion of high temperature molten metal, and reduce the damage of high temperature to the coating and sand core, thereby effectively improving the adhesion and thermal stability of the coating and reducing the defect rate of castings caused by coating problems.
[0026] 2. Dimethyldimethoxysilane can increase the flexibility of silicone resin and its solubility in the system. The methyl group can enhance the physical adsorption between silicone resin and the bonded substrate, making it have better affinity with the substrate surface; methylvinyldichlorosilane introduces vinyl groups into the resin, which can participate in the cross-linking reaction and increase the cross-linking density of the resin, thereby enhancing the hardness and heat resistance of the resin; the phenyl group in phenyltrichlorosilane can improve the thermal stability, oxidation resistance and chemical inertness of silicone resin, while giving the resin a better steric hindrance effect, reducing the freedom of movement of the molecular chain when heated, thereby inhibiting the thermal decomposition caused by excessive movement of the molecular chain, optimizing the performance of the resin in the coating, and thus enabling the silicone resin to better cooperate with the phenolic resin and improve the quality of the sand mud core coating for the inner flow channel of the casting.
[0027] 3. Poly (N-isopropylacrylamide) has unique temperature-sensitive properties. The conformation of its molecular chain will change at different temperatures. During the casting process, when the temperature rises, this change helps the coating to better adapt to the high temperature environment and enhance the thermal stability of the coating. At the same time, poly (N-isopropylacrylamide) can improve the rheological properties of the coating, making the coating easier to distribute evenly during the coating process, thereby improving the adhesion of the coating to the sand core surface, thereby reducing casting defects caused by uneven coating or poor performance at high temperatures, and improving casting quality. DETAILED DESCRIPTION
[0028] The present application discloses a sand-mud core coating for inner flow channel of a casting and a preparation method thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Raw materials description: dimethyldimethoxysilane (CAS No.: 1112-39-6), methylvinyldichlorosilane (CAS No.: 124-70-9), phenyltrichlorosilane (CAS No.: 98-13-5), phenolic resin is thermosetting phenolic resin (CAS No.: 5320-63-1), molecular weight is 10,000, nano-alumina model is ALUNA-80, purchased from Hubei Huifu Nanomaterials Co., Ltd., silicon carbide microsphere model is AM-SiC-Q-1, purchased from Zhejiang Yamei Nano Technology Co., Ltd., silane coupling agent is KH55 0 (CAS No.: 919-30-2), aluminum dihydrogen phosphate (CAS No.: 13530-50-2), water glass (CAS No.: 1344-09-8), mass concentration is 40%, dispersant model is D-425, purchased from Guangzhou Si Tuyuan Chemical Co., Ltd., defoamer model is BYK-022, purchased from Shanghai David New Materials Co., Ltd., zircon powder purchased from Lingshou County Qinglong Mineral Products Co., Ltd., poly N-isopropylacrylamide (CAS No.: 25189-55-3), molecular weight is 50,000, purchased from Hubei Langbowan Biotechnology Co., Ltd.
[0029] Preparation Example 1 Preparation of modified phenolic resin 4.76 kg of dimethyldimethoxysilane, 2.86 kg of methylvinyldichlorosilane and 2.38 kg of phenyltrichlorosilane were dispersed in 30 L of toluene, and stirred evenly at a speed of 200 rpm to obtain a monomer mixture; 5 kg of water was added to the monomer mixture, and stirred at a speed of 200 rpm for 10 min, 0.1 kg of hydrochloric acid was added, and the addition was completed within 1 h, the temperature was raised to 80° C. and stirred at a speed of 200 rpm for 4 h, the solvent was removed by rotary evaporation, and the mixture was washed three times with ethanol and deionized water respectively, and dried in an oven at 60° C. to obtain a silicone resin.
[0030] 15 kg of phenolic resin and 5 kg of silicone resin were mixed and dispersed in 30 L of toluene, stirred at 400 rpm, heated to 120° C. at a rate of 5° C. / min, and reacted for 4 hours. After cooling to below 30° C., the solvent was removed by reduced pressure distillation to obtain a modified phenolic resin.
[0031] Preparation Example 2 Preparation Example 2 is based on Preparation Example 1. The only difference between Preparation Example 2 and Preparation Example 1 is that the amount of dimethyldimethoxysilane used in Preparation Example 2 is 4.35 kg, the amount of methylvinyldichlorosilane used is 2.61 kg, and the amount of phenyltrichlorosilane used is 3.04 kg.
[0032] Preparation Example 3 Preparation Example 3 is based on Preparation Example 1. The only difference between Preparation Example 3 and Preparation Example 1 is that the amount of dimethyldimethoxysilane used in Preparation Example 3 is 4.54 kg, the amount of methylvinyldichlorosilane used is 2.73 kg, and the amount of phenyltrichlorosilane used is 2.73 kg.
[0033] Preparation Example 4 Preparation Example 4 is based on Preparation Example 1. The only difference between Preparation Example 4 and Preparation Example 1 is that the amount of dimethyldimethoxysilane used in Preparation Example 4 is 5.26 kg, the amount of methylvinyldichlorosilane used is 3.16 kg, and the amount of phenyltrichlorosilane used is 1.58 kg.
[0034] Preparation Example 5 Preparation Example 5 is based on Preparation Example 1. The only difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the amount of dimethyldimethoxysilane used is 4 kg, the amount of methylvinyldichlorosilane used is 2.4 kg, and the amount of phenyltrichlorosilane used is 3.6 kg.
[0035] Preparation Example 6 Preparation Example 6 is based on Preparation Example 1. The only difference between Preparation Example 6 and Preparation Example 1 is that methylvinyldichlorosilane is not added in Preparation Example 6.
[0036] Preparation Example 7 Preparation of modified refractory filler Nano-alumina and silicon carbide microspheres are mixed in a mass ratio of 1:0.65, and ultrasonically washed for 30 minutes using an ethanol-water solution with a volume ratio of 1:1. After filtering, the mixture is dried at 60°C for 4 hours to obtain a washed refractory filler. The washed refractory filler is added to a silane coupling agent ethanol solution with a mass content of 2% at a solid-liquid ratio of 1:10, and stirred at 400 rpm for 4 hours. The mixture is transferred to a ball mill and ball-milled at 200 rpm for 4 hours. The solid product is filtered to obtain a solid product, and the solid product is dried in an oven at 60°C to obtain a modified refractory filler.
[0037] Example 1 5 kg of phenolic resin was dispersed in 20 L of solvent, the solvent was an ethanol aqueous solution with a volume fraction of 70%, and the solution was stirred at a speed of 500 rpm until the phenolic resin was completely dissolved to obtain a phenolic resin solution; 12 kg of composite binder was added to the phenolic resin solution, the mass ratio of aluminum dihydrogen phosphate and water glass in the composite binder was 1:0.7, and the solution was stirred at a speed of 800 rpm for 20 minutes at 60°C to obtain a binder solution; 3 kg of dispersant and 1 kg of defoamer were added to the binder solution, and the solution was stirred at a speed of 300 rpm for 10 minutes to obtain a mixed solution; 20 kg of zircon powder and 5 kg of refractory filler were added to the mixed solution, the mass ratio of nano-alumina and silicon carbide microspheres in the refractory filler was 1:0.3, and the solution was ball-milled at a speed of 300 rpm for 1 hour, and then stirred at a speed of 500 rpm for 30 minutes to obtain a casting inner flow channel coated sand mud core coating.
[0038] Example 2 10 kg of phenolic resin was dispersed in 30 L of solvent, the solvent was an ethanol aqueous solution with a volume fraction of 70%, and the solution was stirred at a speed of 500 rpm until the phenolic resin was completely dissolved to obtain a phenolic resin solution; 15 kg of composite binder was added to the phenolic resin solution, the mass ratio of aluminum dihydrogen phosphate and water glass in the composite binder was 1:0.7, and the solution was stirred at a speed of 800 rpm for 20 minutes at 60°C to obtain a binder solution; 5 kg of dispersant and 2 kg of defoamer were added to the binder solution, and the solution was stirred at a speed of 300 rpm for 10 minutes to obtain a mixed solution; 30 kg of zircon powder and 10 kg of refractory filler were added to the mixed solution, the mass ratio of nano-alumina and silicon carbide microspheres in the refractory filler was 1:0.5, and the solution was ball-milled at a speed of 300 rpm for 1 hour, and then stirred at a speed of 500 rpm for 30 minutes to obtain a sand mud core coating for the inner flow channel of the casting.
[0039] Example 3 7.5 kg of phenolic resin was dispersed in 25 L of solvent, the solvent was an ethanol aqueous solution with a volume fraction of 70%, and the solution was stirred at a speed of 500 rpm until the phenolic resin was completely dissolved to obtain a phenolic resin solution; 13.5 kg of composite binder was added to the phenolic resin solution, the mass ratio of aluminum dihydrogen phosphate and water glass in the composite binder was 1:0.7, and the solution was stirred at a speed of 800 rpm for 20 minutes at 60°C to obtain a binder solution; 4 kg of dispersant and 1.5 kg of defoamer were added to the binder solution, and the solution was stirred at a speed of 300 rpm for 10 minutes to obtain a mixed solution; 25 kg of zircon powder and 7.5 kg of refractory filler were added to the mixed solution, the mass ratio of nano-alumina and silicon carbide microspheres in the refractory filler was 1:0.4, and the solution was ball-milled at a speed of 300 rpm for 1 hour, and then stirred at a speed of 500 rpm for 30 minutes to obtain a casting inner flow channel coated sand mud core coating.
[0040] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the phenolic resin is replaced by the modified phenolic resin prepared in Preparation Example 1.
[0041] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the phenolic resin is replaced by the modified phenolic resin prepared in Preparation Example 2.
[0042] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the phenolic resin is replaced by the modified phenolic resin prepared in Preparation Example 3.
[0043] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the phenolic resin is replaced by the modified phenolic resin prepared in Preparation Example 4.
[0044] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the phenolic resin is replaced by the modified phenolic resin prepared in Preparation Example 5.
[0045] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the phenolic resin is replaced by the modified phenolic resin prepared in Preparation Example 6.
[0046] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that the mass ratio of nano-alumina and silicon carbide microspheres in Example 10 is 1:0.1.
[0047] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that the mass ratio of nano-alumina and silicon carbide microspheres in Example 11 is 1:0.7.
[0048] Example 12 Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, the refractory filler is replaced by the modified refractory filler prepared in Preparation Example 7.
[0049] Embodiment 13 Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that the raw materials prepared in Example 13 also include 1% poly (N-isopropylacrylamide).
[0050] 7.5 kg of phenolic resin was dispersed in 25 L of solvent, the solvent was an ethanol aqueous solution with a volume fraction of 70%, and the solution was stirred at a speed of 500 rpm until the phenolic resin was completely dissolved to obtain a phenolic resin solution; 13.5 kg of composite binder and poly (N-isopropylacrylamide) were added to the phenolic resin solution, the mass ratio of aluminum dihydrogen phosphate and water glass in the composite binder was 1:0.7, and the solution was stirred at a speed of 800 rpm for 20 minutes at 60°C to obtain a binder solution; 4 kg of dispersant and 1.5 kg of defoamer were added to the binder solution, and the solution was stirred at a speed of 300 rpm for 10 minutes to obtain a mixed solution; 25 kg of zircon powder and 7.5 kg of refractory filler were added to the mixed solution, the mass ratio of nano-alumina and silicon carbide microspheres in the refractory filler was 1:0.4, and the solution was ball-milled at a speed of 300 rpm for 1 hour, and then stirred at a speed of 500 rpm for 30 minutes to obtain a casting inner flow channel coated sand mud core coating.
[0051] Embodiment 14 Example 14 is based on Example 13. The only difference between Example 14 and Example 3 is that the added amount of poly (N-isopropylacrylamide) in Example 14 accounts for 3% of the total mass.
[0052] Embodiment 15 Example 15 is based on Example 13. The only difference between Example 15 and Example 3 is that the added amount of poly (N-isopropylacrylamide) in Example 15 accounts for 2% of the total mass.
[0053] Example 16 Example 16 is based on Example 13. The only difference between Example 16 and Example 3 is that the added amount of poly (N-isopropylacrylamide) in Example 16 accounts for 6% of the total mass.
[0054] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that the composite binder in Comparative Example 1 is replaced by aluminum dihydrogen phosphate.
[0055] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that the composite binder in Comparative Example 2 is replaced by water glass.
[0056] Performance testing Select "JB / T 8583-2008 Coated Sand for Foundry" as the standard, and use a tensile testing machine to test the room temperature tensile strength of the sample; place the sample in a high temperature furnace at 1000℃ to test its collapse time. Prepare three samples for each sample, take the average value after measurement, and record the results in Table 1.
[0057] Table 1 Test results of tensile strength and heat resistance time of coated sand mud core coating at room temperature It can be seen from Table 1 that the room-temperature tensile strength of Examples 1-3 is greater than 4.4 MPa, and the heat-resistant time is greater than 213 s. It can be seen that the coated sand mud core coating prepared in the present application has high room-temperature tensile strength and long heat-resistant time, and the coating has good adhesion and thermal stability.
[0058] As can be seen from Table 1, the only difference between Example 4-9 and Example 3 is that the phenolic resin in Example 4-9 is replaced by a modified phenolic resin. Compared with Example 3, the room temperature tensile strength and heat resistance time of Example 4-9 are increased; this is because the use of silicone resin to modify the phenolic resin can effectively improve the adhesion and heat resistance of the phenolic resin; Example 4-6 is modified within a limited range and has a good modification effect. After the limited ratio is destroyed in Examples 7 and 8, the modification effect is reduced; Example 9 reduces the synthetic components of the silicone resin, the synergistic effect between the components is weakened, and the modification effect is further reduced.
[0059] As can be seen from Table 1, the only difference between Examples 10-12 and Example 3 is that: in Example 10, the mass ratio of nano-alumina and silicon carbide microspheres is 1:0.1, and in Example 11, the mass ratio of nano-alumina and silicon carbide microspheres is 1:0.7. In Example 12, the refractory filler is replaced with the modified refractory filler prepared in Preparation Example 7. Compared with Example 3, Examples 10 and 11 have decreased tensile strength at room temperature and heat resistance time; this is because the limited ratio is destroyed and the synergistic effect of the two fillers is reduced; the tensile strength at room temperature and heat resistance time of Example 12 are increased, because the dispersibility of the refractory filler is increased through the modification treatment, thereby improving the performance of the coating, thereby improving the adhesion performance and heat resistance performance.
[0060] As can be seen from Table 1, the only difference between Examples 13-16 and Example 3 is that: Poly (N-isopropylacrylamide) is added to Examples 13-16, and the amount of addition is regulated. Compared with Example 3, the adhesion performance and heat resistance of Examples 13-16 are improved; Examples 13-15 are added within a limited range, and have good performance improvement; Example 16 increases the amount of addition, and the performance decreases. This is because too much poly (N-isopropylacrylamide) affects the fluidity of the coating, destroys the balance between the components, and affects the stability of the structure, thereby reducing the adhesion performance and heat resistance.
[0061] As can be seen from Table 1, the only difference between Comparative Examples 1 and 2 and Example 3 is that: Comparative Example 1 replaces the composite binder with aluminum dihydrogen phosphate, and Comparative Example 2 replaces the composite binder with water glass. Compared with Example 3, the room temperature tensile strength and heat resistance time of Comparative Examples 1 and 2 are greatly reduced; this is because the lack of the synergistic effect of aluminum dihydrogen phosphate and water glass reduces the stability of the internal structure of the coating, and the adhesion performance and thermal stability performance are reduced.
[0062] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A sand-mud core coating for inner flow channel of a casting, characterized in that: The composition includes the following components in parts by weight: Phenolic resin 5-10 parts Composite adhesive 12-15 parts Dispersant 3-5 parts 1-2 parts of defoamer Zircon powder 20-30 parts Refractory filler 5-10 parts 20-30 parts of solvent; The composite binder comprises aluminum dihydrogen phosphate and water glass.
2. The sand-mud core coating for inner flow channel of a casting according to claim 1, characterized in that: The phenolic resin is subjected to modification treatment to obtain a modified phenolic resin, and the raw materials for preparing the modified phenolic resin include a phenolic resin body and an organosilicon resin.
3. The sand-mud core coating for inner flow channel of casting according to claim 2, characterized in that: The raw materials for preparing the organic silicon resin include dimethyldimethoxysilane, methylvinyldichlorosilane and phenyltrichlorosilane.
4. The sand-mud core coating for inner flow channel of a casting according to claim 3, characterized in that: The mass ratio of the dimethyldimethoxysilane, methylvinyldichlorosilane and phenyltrichlorosilane is 1:0.6:(0.5-0.7).
5. The sand-mud core coating for inner flow channel of casting according to claim 1, characterized in that: The refractory filler comprises nano-alumina and silicon carbide microspheres.
6. The sand-mud core coating for inner flow channel of casting according to claim 5, characterized in that: The mass ratio of the nano-alumina to the silicon carbide microspheres is 1:(0.3-0.5).
7. The sand-mud core coating for inner flow channel of casting according to claim 6, characterized in that: The refractory filler is subjected to modification treatment to obtain a modified refractory filler, and the modified refractory filler is prepared by the following steps: The nano-alumina and silicon carbide microspheres are mixed, ultrasonically washed with an ethanol aqueous solution, filtered and dried to obtain a washed refractory filler; the washed refractory filler is added to a silane coupling agent ethanol solution, stirred for reaction, ball milled, filtered to obtain a solid product, and dried to obtain a modified refractory filler.
8. The sand-mud core coating for inner flow channel of casting according to claim 1, characterized in that: The raw materials for preparing the sand mud core coating for coating the inner flow channel of the casting also include poly N-isopropyl acrylamide.
9. The sand-mud core coating for inner flow channel of casting according to claim 8, characterized in that: The added amount of the poly (N-isopropylacrylamide) is 1-3% of the total mass.
10. A method for preparing a sand-mud core coating for inner flow channel of a casting as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: The phenolic resin is dispersed in a solvent and stirred until the phenolic resin is completely dissolved to obtain a phenolic resin solution; a composite binder is added to the phenolic resin solution, heated and stirred to obtain a binder solution; a dispersant and a defoamer are added to the binder solution and stirred to obtain a mixed solution; zircon powder and a refractory filler are added to the mixed solution, ball-milled and stirred to obtain a sand mud core coating for the inner flow channel of the casting.